PERLINDUNGAN HUKUM TERHADAP EKSPLOITASI EKONOMI ANAK JALANAN DALAM PERSPEKTIF HUKUM PERLINDUNGAN ANAK - Muhammad Gunawan Sadjali (RechtIdee, 2021)
The problem of street children is a form of violation of children's rights. Fulfillment of children's rights is a top priority that must be fulfilled in relation to guarantees of legal protection and fulfillment of children's rights as stated in the Convention on the Rights of the Child. This study uses a normative legal method with a statutory approach (statue approach) and a conceptual approach (conceptual approach). Sources of data used are primary and secondary legal materials, data collection techniques using interviews. The results of this study indicate that the legal basis for the protection of street children can refer to the law on child protection and local regulations of the City of Mojokerto regarding the protection of street children and the welfare of the elderly. However, the implementation is not optimal because the legal protection provided to street children is still repressive. Even though legal protection is repressive in nature, the provision of criminal sanctions and imprisonment still requires preventive legal protection efforts. Preventive legal protection can be carried out by collaborating with the young Majapahit movement community to provide preventive legal protection efforts through: mental-spiritual guidance, skills training, sex education, and educational funding assistance.Keywords: Street Children, Economic Exploitation, Legal Protection